Development of an interprofessional competency framework in Japan. Issue 5 (2nd September 2016) - Haruta, Junji; Sakai, Ikuko; Otsuka, Mariko; Yoshimoto, Hisashi; Yoshida, Kazue; Goto, Michiko; Shimoi, Toshinori
ABSTRACT: This article presents a project that aimed to identify a set of competencies (domains and statements) to prepare Japanese students and healthcare practitioners for collaborative practice. The Japan Association for Interprofessional Education (JAIPE) has started a government-funded project to formulate its interprofessional competency framework, in cooperation with professional organisations (e.g. Japan Society for Medical Education) in healthcare and social sciences. This three-year project is underway as part of the Initiative to Build up the Core Healthcare Personnel programme of Mie University. This project consists of five stages: literature review, data collection, prototype development, consensus formation, and finalisation. Our efforts will culminate in Japan's first interprofessional competency framework, with consensus from relevant academic societies and other stakeholders. We hope that the involvement of stakeholder participation will improve the usability of the final interprofessional competency framework.